Using reflective teaching to develop students’ teaching skill - Rozimela, Yenni (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2013)
This study was conducted to explain the extent to which reflective teaching and peer comments were able to develop students’ teaching skills. It employed classroom action research involving a group of students enrolled in a Microteaching course at the English Department of Universitas Negeri Padang (State University of Padang) during the first semester (January–June) of the 2012 academic year. The data were collected through observation notes, self-reflection notes, teaching tasks, and questionnaires, and were analyzed descriptively. The results showed improvements in students’ teaching skills across all assessed aspects. Furthermore, the students demonstrated positive perceptions of reflective teaching through self-reflection and peer comments.